Economic Studies in Bologna: A Historical Introduction - Roberto Scazzieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1988)
Interest in economic issues at Bologna goes back to the earliest period of University history. It is among law scholars that economic life became a subject for intellectual inquiry.
Keywords: 330